Membangun Karakter Siswa Melalui Pendekatan Integratif Dalam Pembelajaran Akidah Akhlak: Studi Kasus Di SMA Negeri 1 Padang Panjang - Romi Muliawarman; Fadriati (Universitas Majalengka, 2025)
Aqidah Akhlak learning has a strategic role in shaping the character of students who are religious and have noble morals. However, the integration between cognitive, affective, and psychomotor aspects in the learning process is still often neglected. This study aims to examine the application of an integrative approach in Aqidah Akhlak learning and its contribution to the formation of student character at SMA Negeri 1 Padang Panjang. The method used is a field study with a qualitative approach and data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the integrative approach has been implemented through active and contextual learning models, supported by various school religious programs. This approach has been proven to contribute positively to changes in student attitudes and behavior, both in terms of faith and morals. This finding strengthens the importance of a holistic PAI learning design in building student character.